Sternal Abnormalities on Thoracic Radiographs of Dogs and Cats - Dirk H. N. van den Broek; Siemone C. Vester; Mauricio Tobón Restrepo; Stefanie Veraa (Animals, 2023)
Evaluation of the sternum is part of the routine examination of small animal thoracic radiographs. However, descriptions on frequency and type of abnormalities are lacking. This retrospective observational study aimed to describe abnormal radiographic findings of the sternum in a cross-section of client-owned dogs and cats undergoing thoracic radiography between 1 January 2019 and 1 January 2021 for reasons unrelated to diseases of the sternum. The study population consisted of 777 dogs (mean age, 7.3 ± 3.9 years) and 183 cats (mean age, 7.3 ± 5.1 years). Sternal abnormalities were observed in 189/777 (24%) dogs and 53/183 (29%) cats, mostly around the intersternebral cartilages, accounting for 32/80 (40%) dogs and 20/35 (57%) cats. This was followed by an abnormal number of sternal segments (8% dogs, range 3–9 sternebrae; 15% cats, range 7–9 sternebra). Pectus excavatum was observed in 6/777 (0.8%) dogs and 6/183 (3%) cats, and pectus carinatum in 18/777 (2%) dogs and 2/183 (1%) cats. Post-traumatic changes, such as subluxation, were observed in nine dogs (1.1%) and three cats (1.6%). Presumed prostatic carcinoma metastasis and malignant lymphoma were observed in two dogs (0.2%). Incidental radiographic sternal abnormalities are common in cats and dogs but mostly of unknown clinical relevance.